Gambling in digital games and esports: a scoping review - Mattinen Topias; Macey Joseph; Hamari Juho (United States, 2025)
The convergence of gaming and gambling has become increasingly prominent in recent years, most notably in the context of esports. Consequently, there has been a recent surge of literature investigating this phenomenon. This convergence is often driven by the commercial advantages it offers, yet there are concerns over the effects of mixing gambling with gaming, both in relation to the quality of experiences, and possible ethical problems. In this scoping review of the related corpus, we explore the development of work addressing the presence of gambling associated with digital games; examining methodologies, research topics, the specific gambling activities addressed, and identifying gaps present in the field. The body of literature reviewed consists of peer-reviewed, English language publications (n=132). Our findings indicate a sharp increase in yearly publications in the late 2010s, attributed partly due to rising interest in novel gambling activities, such as loot boxes. We recommend future research incorporates both qualitative and mixed methods research to provide the field with results unavailable at current time.
Proceedings of the 56th Annual Hawaii International Conference on System Sciences